2020
DOI: 10.1177/2319510x19898633
|View full text |Cite
|
Sign up to set email alerts
|

Linear and Nonlinear Causal Relationships Between International Reserves and Economic Growth: Evidence from India

Abstract: This study investigates linear and nonlinear causal relationships between accumulated international reserves (IR) and economic growth (Econ) in the case of India. The present study is carried out using quarterly data ranging from the period of the first quarter of 1985 to the fourth quarter of 2014. The study used econometric tools such as the augmented Dickey–Fuller (ADF) unit root test, the linear Granger causality test, Johansen’s cointegration test, the Brock, Dechert and Scheinkman (BDS) test and the nonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The outcome is in line with the general belief that effective management of foreign reserves can play a crucial role in promoting Nigerian economy. This discovery corroborates the findings of Kashif and Sridharan (2015), who observed a substantial positive influence of holding foreign reserves on long-term economic growth in Malaysia, India, and Brazil, respectively.…”
Section: Resultssupporting
confidence: 90%
“…The outcome is in line with the general belief that effective management of foreign reserves can play a crucial role in promoting Nigerian economy. This discovery corroborates the findings of Kashif and Sridharan (2015), who observed a substantial positive influence of holding foreign reserves on long-term economic growth in Malaysia, India, and Brazil, respectively.…”
Section: Resultssupporting
confidence: 90%
“…The growth in GDP is unable to promote foreign exchange earnings in the country. Finally, Kashif (2016) examined the linear and nonlinear relationship between international reserves and economic growth in Algeria. The study found that there is bidirectional causality between international reserves and economic growth with respect to linear causality but a unidirectional causality exists running from economic growth to international reserves with respect to nonlinear causality.…”
Section: Causal Relationship Between Foreign Exchange Reserve and Eco...mentioning
confidence: 99%
“…Panda and Trivedi (2016) performed a study using quarterly data from 1996 to 2014; they have reported that foreign exchange reserves with RBI show a positive long-run relationship with money supply and trade openness and a negative long-run relationship with exchange rate volatility. Kashif and Sridharan (2015) performed a study on India’s reserves and have reported that economic growth is positively associated with IR, while trade openness is positively associated with IR. More recently, Nayak and Baig (2019) have conducted a study on factors influencing IR by using a long-run model, which was prepared by following a buffer stock model proposed by Frenkel and Jovanovic (1981).…”
Section: Review Of the Literaturementioning
confidence: 99%